An assessment of industry-academe-government linkages in the area of health research and development (2005-2009) - Pernitez-Agan, Sweetmavourneen Uy (University of the Philippines Diliman, 2010)
Health research and development has long been proven to be an essential component in the economic development of a country. However, health research requires a well-structured and supportive environment for it to make a dent in the health and economy of a country. Developing countries are still struggling to keep up with the international standard of budget allocation for health research. In the Philippines, the total health research and development expenditures remain far below the World Health Organization's recommended level of five percent of the total health expenditures. It is therefore important to maximize available resources and to prevent duplication of health research efforts. Dr. Jaime Montoya, Executive Director of the Philippine Council for Health Research and Development (PCHRD), said that one practical approach is to increase cooperation between the national programs and health initiatives to address common problems. This kind of cooperation creates 'new funding' by focusing the attention of existing activities on common goals. This approach fosters participative democracy and a spirit of community responsibility to contribute to the overall good. Lead government bodies in health research made a move by establishing the Philippine National Health Research System (PNHRS) through the signing of a Memorandum of Agreement in March 2003. The PNHRS aims to : promote and enhance cooperation between and among the organizations and networks within the PNHRS; to develop capacities for knowledge production, use and management, research management and financing; and to avoid duplication, thus deliver solutions with greater impact to the pressing health problems of the country. The efforts behind and within the functioning PNHRS is one of several existing collaborations led by PCHRD. This paper attempts to come up with an assessment of the present linkages/ partnerships among the government, university and industry (GUI) in the area of health research and development as well as come up with recommendations to enhance and further build a strong fulfilling partnership or linkages. This study is mainly descriptive in design. Three approaches were done by the student in the implementation of the study. First approach was the gathering of primary and secondary data. Second approach is the organization and analysis of gathered data and the third approach was the development of recommendation or action points. Among the 34 submitted questionnaires, only 19 survey forms were completed. Of the 19, only three were from the industry, 11 were from the government (three were of the same agency but different departments), and five were from the academe.